Ion cyclotron instabilities in multicomponent magnetic field-aligned plasma flow with shear velocity flow - Chibisov, D.V. (Вопросы атомной науки и техники, 2013)
The ion cyclotron instabilities of magnetic-field-aligned multi-species plasma flow with the flow velocity shear are investigated. It is assumed that plasma consist of two ion species, H⁺ and O⁺, the most often occurring in the Earth's ionosphere. The effect of the hydrogen ions on the ion kinetic as well as hydrodynamic shear-flow-driven ion cyclotron instabilities with the frequency approximately equal to the cyclotron frequency of the O⁺ ions is considered. Досліджено іонні циклотронні нестійкості багатокомпонентного потоку плазми вздовж магнітного поля зі зсувом потокової швидкості. Припускається, що до складу плазми входять іони двох видів, H⁺ і O⁺, найбільш поширених в іоносфері Землі. Розглядається вплив іонів водню на іонну кінетичну і гідродинамічну іонні циклотронні нестійкості, що збуджуються широм потокової швидкості, з частотами коливань приблизно рівними циклотронній частоті іонів O⁺. Исследованы ионные циклотронные неустойчивости многокомпонентного потока плазмы вдоль магнитного поля со сдвигом потоковой скорости. Предполагается, что в состав плазмы входят ионы двух видов, H+ и O+, наиболее распространенных в ионосфере Земли. Рассматривается влияние ионов водорода на возбуждаемые широм потоковой скорости ионную кинетическую и гидродинамическую ионные циклотронные неустойчивости с частотами колебаний приблизительно равными циклотронной частоте ионов O+.